Overview of osteoporosis in HIV patients - Tello-Cajiao, Maria Elena; Riveros Bermudez, Sonia Dayana; Abreu Lomba , Alin (Interdisciplinary Journal of Epidemiology and Public Health, 2024)
Introduction: Human immunodeficiency virus (HIV) infection is an important public health problem. Antiretroviral therapy has significantly improved patient survival; as a consequence, the chronicity of the infection has led to several complications, including alterations in bone mineral metabolism. Objective: Summarize the main factors that affect bone health in HIV patients and result in an increased risk of osteoporosis and fracture in this population. Methods: A narrative review of the main factors that alter bone mineral metabolism in HIV patients was performed. Results: Bone mineral metabolism in the HIV patient is affected by traditional modifiable factors such as vitamin D deficiency and non-modifiable factors such as age. However, the presence of the virus, the host immune inflammatory response and retroviral therapy may also decrease bone mineral density. Conclusion: Early identification and intervention of factors affecting bone health in HIV-infected patients is imperative to reduce the risk of osteoporosis and fractures.